Zakat & Transformasi Digital: Upaya Membangkitkan Kesadaran Masyarakat Muslim Perkotaan - Ariyadi, Ariyadi; Sanawiah, Sanawiah; Ningsih, Salsabila Hady (Lembaga Yasin AlSys, 2025)
Digital transformation has changed various aspects of life, including zakat management. This study aims to analyze the awareness and participation of urban Muslim communities in digital zakat as well as the challenges faced. Using descriptive qualitative method, this research involved 50 respondents in Palangka Raya through interview, observation, and documentation. The results show that the majority of respondents understand the benefits of digital zakat which is more practical than conventional methods. However, there are still doubts regarding the validity of Islamic law, transparency, and transaction security. The habit factor and limited digital literacy are also the main obstacles. Therefore, wider socialization, security system improvement, and transparency in digital zakat management are needed. With this effort, digital zakat is expected to be more accepted and optimized as a modern solution in the collection and distribution of zakat.